Patent foramen ovale in trigeminal autonomic cephalalgias and hemicrania continua: a non-specific pathophysiological occurrence? Foramen oval patente em cefaleias trigêmino-autonômicas e hemicrania contínua: uma ocorrência fisiopatológica não específica? - Vanise Amaral (Arquivos de Neuro-Psiquiatria, 2010)
Patent foramen ovale (PFO), a relatively common abnormality in adults, has been associated with migraine. Few studies also linked PFO with cluster headache (CH). To verify whether right-to-left shunt (RLS) is related to headaches other than migraine and CH, we used transcranial Doppler following microbubbles injection to detect shunts in 24 CH, 7 paroxysmal hemicrania (PH), one SUNCT, two hemicrania continua (HC) patients; and 34 matched controls. RLS was significantly more frequent in CH than in controls (54% vs. 25%, p=0.03), particularly above the age of 50. In the HC+PH+SUNCT group, RLS was found in 6 patients and in 2 controls (p=0.08). Smoking as well as the Epworth Sleepiness Scale correlated significantly with CH, smoking being more frequent in patients with RLS. PFO may be non-specifically related to trigeminal autonomic cephalalgias and HC. The headache phenotype in PFO patients probably depends on individual susceptibility to circulating trigger factors. O forame oval patente (FOP), uma anormalidade cardíaca relativamente comum em adultos, tem sido associado à enxaqueca, mas raramente às cefaléias trigêmino-autonômicas (TACs). Utilizamos o Doppler transcraniano (DTC) para detecção de shunt direito-esquerdo (SDE) em 24 pacientes com cefaléia em salvas (CS), sete com hemicrania paroxística (HP), dois com hemicrania continua (HC) e um com SUNCT; alem de 34 controles. O SDE foi mais frequente nos pacientes com CS do que nos controles (54% vs. 25% p=0,03), particularmente acima de 50 anos. No grupo HP+HC+SUNCT, o SDE foi encontrado em seis pacientes e dois controles (p=0,08). O hábito de fumar, bem como sonolência excessiva diurna foram mais frequentes em paciente com CS. O FOP pode ter importância inespecífica na fisiopatologia das TACs e HC, na dependência da susceptibilidade individual a fatores desencadeantes.